1973
DOI: 10.1007/bf01221853
|View full text |Cite
|
Sign up to set email alerts
|

Genetic selection for high and low fasting blood glucose levels in mice. I. Fasting blood glucose levels, glucose tolerance and isolated tissue studies

Abstract: Swiss-Hauschka mice have been selected for high (HG) and low (LG) fasting blood glucose (FBG) levels for four generations. All rantings were brother to sister. Differences in mean FBG levels have remained relatively constant (20 to 30 rag~ between the two lines since initiation of selection (p < 0.001). Body weights have declined more rapidly with inbreeding in the LG line as compared to the HG line through Fs, but no further decline was noted in the Fa generation. Fasting serum immunoreactivo insulin (It~I) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
1988
1988

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This high mutation rate may explain the observation that multiple loci determine the difference in glucose tolerance in the inbred mouse strains examined. On the other hand, Gleason et al (22) observed multiple alleles for glucose tolerance within one inbred strain, suggesting that most of the genetic differences between inbred strains are preexistent in a wild population, with alternative alleles fixed by inbreeding.…”
Section: K Kaku and Associatesmentioning
confidence: 95%
See 1 more Smart Citation
“…This high mutation rate may explain the observation that multiple loci determine the difference in glucose tolerance in the inbred mouse strains examined. On the other hand, Gleason et al (22) observed multiple alleles for glucose tolerance within one inbred strain, suggesting that most of the genetic differences between inbred strains are preexistent in a wild population, with alternative alleles fixed by inbreeding.…”
Section: K Kaku and Associatesmentioning
confidence: 95%
“…Given this background of complexity for human diabetes, investigators have used inbred mouse strains for genetic analysis (18)(19)(20)(21)(22)(23)(24)(25)(26). An inbred mouse strain represents an almost limitless resource of genetically identical individuals that are predominantly homozygous at every locus (27).…”
mentioning
confidence: 99%